Effect of 16% Carbamide Peroxide Bleaching Gel on Enamel and Dentin Surface Micromorphology and Roughness of Uremic Patients: An Atomic Force Microscopic Study - Mahmoud, Salah Hasab; Elembaby, Abeer El Sayed; Zaher, Ahmed Ragheb; Grawish, Mohammed El-Awady; Elsabaa, Heba M; El- Negoly, Salwa Abd El-Raof; Sobh, Mohamed Abdel Kader (European Journal of Dentistry, 2010)
Objectives: To investigate the effect of 16% carbamide peroxide bleaching gel on surface micromorphology and roughness of enamel and root dentin of uremic patients receiving hemodialysis using atomic force microscopy (AFM).Methods: A total of 20 sound molars were collected from healthy individuals (n=10) and uremic patients (n=10). The roots were separated from their crowns at the cemento-enamel junction. Dental slabs (3 mm x 2 mm x 2 mm) were obtained from the buccal surface for enamel slabs and the cervical third of the root surface for dentin slabs. Dental slabs were then flattened and serially polished up to #2500-grit roughness using silicon carbide abrasive papers. Half of the slabs obtained from healthy individuals and uremic patients were stored in artificial saliva and left without bleaching for control and comparison. The remaining half was subjected to a bleaching treatment using 16% carbamide peroxide gel (Polanight, SDI Limited) 8 h/day for 14 days and stored in artificial saliva until AFM analysis was performed. Statistical analysis of the roughness average (Ra) results was performed using one-way ANOVA and Bonferroni post hoc multiple comparisons test.Results: The micromorphological observation of bleached, healthy enamel showed exaggerated prism irregularities more than non-bleached specimens, and this observation was less pronounced in bleached uremic enamel specimens with the lowest Ra. Bleached healthy dentin specimens showed protruded peritubular dentin and eroded intertubular dentin with the highest Ra compared to bleached uremic dentin.Conclusions: The negative effects of the bleaching gel on uremic tooth substrates are less dramatic and non-destructive compared to healthy substrates because uremia confers different micromorphological surface changes. (Eur J Dent 2010;4:175-181)
Keywords: Bleaching; Atomic force microscopy; Uremic patients; Carbamide peroxide; Chronic renal failure